Cost and profit conditions in the Hungarian intensive apple production - Apáti, F.; Wang, X.; Racskó, J. (International Journal of Horticultural Science, 2007)
In this study I investigated the cost and profit conditions and the efficiency of intensive, qualitative apple production on the basis of a data collection carried out in ventures of high standard production. I concluded that the intensive apple production has an extremely high cost requirement, the production costs are approximately 1500 to 1600 thousand HUF per hectare. In an average case, a production value of 2000 thousand HUF per hectare may be reached, which may fluctuate in a wide interval during the years. Considering the above mentioned, a net profit of 400 to 500 thousand HUF may be realized in one hectare. It should be highlighted that regarding the present marketing conditions, realizing the appropriate profit may be expected only by producing 30 to 40 tons per hectare yields and 80 to 90% food quality ratio.